Orphan nuclear receptor SHP regulates iron metabolism through inhibition of BMP6-mediated hepcidin expression - Kim, Don-Kyu; Dooley, Steven; Muckenthaler, Martina (Scientific reports, 2016)
Small heterodimer partner (SHP) is a transcriptional corepressor regulating diverse metabolic processes. Here, we show that SHP acts as an intrinsic negative regulator of iron homeostasis. SHP-deficient mice maintained on a high-iron diet showed increased serum hepcidin levels, decreased expression of the iron exporter ferroportin as well as iron accumulation compared to WT mice. Conversely, overexpression of either SHP or AMP-activated protein kinase (AMPK), a metabolic sensor inducing SHP expression, suppressed BMP6-induced hepcidin expression. In addition, an inhibitory effect of AMPK activators metformin and AICAR on BMP6-mediated hepcidin gene expression was significantly attenuated by ablation of SHP expression. Interestingly, SHP physically interacted with SMAD1 and suppressed BMP6-mediated recruitment of the SMAD complex to the hepcidin gene promoter by inhibiting the formation of SMAD1 and SMAD4 complex. Finally, overexpression of SHP and metformin treatment of BMP6 stimulated mice substantially restored hepcidin expression and serum iron to baseline levels. These results reveal a previously unrecognized role for SHP in the transcriptional control of iron homeostasis.
Gesehen am 25.02.2019